- (+) x (+) =
- (-) x (-) =
- (+) x (-) =
- (-) x (+) =

- (+) / (+) =
- (-) / (-) =
- (+) / (-) =
- (-) / (+) =

*(a) A*

**positive**number multiplied by another**positive**number gives a__positive__answer.

(b) A

**Eg, 6 x 6 = 36**(b) A

**negative**number multiplied by another**negative**number gives a__positive__answer.

**Eg, (-6) x (-6) = 36***(c) A*

**positive**number multiplied by a**negative**number gives a__negative__answer.

(d) A

**Eg, 6 x (-6) = (-36)**(d) A

**negative**number multiplied by a**positive**number gives a__negative__answer.

**Eg, (-6) x 6 = (-36)***(e) A*

**positive**number divided by another**positive**number gives a__positive__number

**Eg, 6 / 6 = 1***(f) A*

**negative**number divided by another**negative**number gives a__negative__number.

**Eg, (-6) / (-6) = 1***(g) A*

**positive**number divided by a**negative**number gives a__negative__number.

**Eg, 6 / (-6) = (-1)***(h) A*

**negative**number divided by a**positive**number gives a__negative__number.

**Eg, (-6) / (6) = (-1)**
## 0 comments:

## Post a Comment